Mucin Expression in Endoscopic Ultrasound-Guided Fine-Needle Aspiration Specimens Is a Useful Prognostic Factor in Pancreatic Ductal Adenocarcinoma. Issue 5 (July 2015) - Higashi, Michiyo; Yokoyama, Seiya; Yamamoto, Takafumi; Goto, Yuko; Kitazono, Ikumi; Hiraki, Tsubasa; Taguchi, Hiroki; Hashimoto, Shinichi; Fukukura, Yoshihiko; Koriyama, Chihaya; Mataki, Yuko; Maemura, Kosei; et al.
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to further examine the utility of mucin (MUC) expression profiles as prognostic factors in pancreatic ductal adenocarcinoma (PDAC). Methods Mucin expression was examined by immunohistochemistry analysis in endoscopic ultrasound-guided fine-needle aspiration specimens obtained from 114 patients with PDAC. The rate of expression of each MUC was compared with clinicopathologic features. Results The expression rates of MUCs in cancer lesions were MUC1, 87.7%; MUC2, 0.8%; MUC4, 93.0%; MUC5AC, 78.9%; MUC6, 24.6%; and MUC16, 67.5%. MUC1 and MUC4 were positive, and MUC2 was negative in most PDACs. Patients with advanced stage of PDAC with MUC5AC expression had a significantly better outcome than those who were MUC5AC-negative (P = 0.002). With increasing clinical stage, total MUC6 expression decreased (P for trend = 0.001) and MUC16 cytoplasmic expression increased (P for trend = 0.02). The prognosis of patients with MUC16 cytoplasmic expression was significantly poorer than those without this expression. Multivariate survival analysis revealed that MUC16 cytoplasmic expression was a significant independent predictor of a poor prognosis after adjusting for the effects of other prognostic factors (P = 0.002). Conclusions Mucin expression profiles in ultrasound-guided fine-needle aspiration specimens have excellent diagnostic utility and are useful predictors of outcome in patients with PDAC.